Organizational Learning for Strengthening Village Officials’ Digital Competence: A Case Study of the Village Information System - Yunus, Asraf; Saprul, Saprul; Muthalib, Abdul Azis (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
Village digitalization depends not only on infrastructure but also on officials’ capacity to learn and use digital systems. This study analyzes the digital competence of officials in Besu Village and develops an organizational learning framework for strengthening the use of the Village Information System (SID). A qualitative case-study design combined in-depth interviews, participatory observation, and document analysis involving the Village Secretary, Head of General and Administrative Affairs, and SID Operator. Thematic analysis revealed four patterns: digital knowledge and operational skills were concentrated in the operator; routine rather than advanced features dominated system use; fear of error and low confidence inhibited independent practice; and one-off training did not generate sustained knowledge transfer. The study proposes the BELAJAR-SID framework, integrating baseline assessment, tiered education, task-based practice, workplace mentoring, communities of practice, and competence review. The findings demonstrate that workplace learning arrangements are essential for converting individual technical expertise into distributed organizational capability and for reducing service dependence on a single operator.